Kształtowanie roli poczty polskiej w projektowanym systemie doręczeń elektronicznych — racjonalny ustawodawca czy krawiec „szyjący na miarę”? - Galewska, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
A model adopted in the Act on Electronic Deliveries is based on the activity of the postal operator that is called designated operator and that provides universal services as well as the public service of registered electronic delivery and public hybrid service. Qualified providers of trust services are to provide qualified services of registered electronic delivery acting next to a designated operator. The intention of the drafter is to adopt a model aimed at creating a competitive market. However, a prominent role of a designated operator in the Act on Electronic Deliveries contradicts this idea.
Keywords: postal services; designated operator; competition; internal market; electronic deliveries